THE INFLUENCE OF THE USE OF ICT ON LEARNING ACHIEVEMENT OF AQIDAH AHLAK - Mulyoto, M; Mujiburrohman, M; Subando, Joko (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
The purpose of this study was to determine the effect of the use of ICT on learning achievement in Aqeedah Akhlak lessons. The method used is quantitative with a correlational approach. Data collection was carried out using observation techniques, documentation and questionnaires. The results showed that the use of ICT, learning motivation, and student learning outcomes at MI Muhammadiyah Walen 1 were in the sufficient category. Partially, the use of ICT has a significant effect on student learning outcomes of 0.236, included in the